1989
DOI: 10.1128/aac.33.7.1042
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole (UK-49,858) treatment of candidiasis in normal and diabetic rats

Abstract: Fluconazole (UK-49,858), a new oral bistriazole antifungal agent, was compared with amphotericin B in the treatment of established systemic infection with Candida albicans in normal and diabetic rats. In normal rats, oral fluconazole at 10 mg/kg per day for 7 days reduced Candida colony counts in the kidneys and livers as well as amphotericin B did and was nearly as effective as amphotericin B in a 21-day treatment trial. There was no further reduction in Candida colony counts when normal rats were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…One of these antifungal agents is the triazole fluconazole (Flu) (4,10,14,33,34,41). In vivo experimental studies suggested that Flu is active against disseminated candidiasis (8,9,29,31,32,35,37). Recently, the antifungal efficacy of Flu was demonstrated in persistently granulocytopenic rabbits when it was used for prevention or early treatment (39,40).…”
mentioning
confidence: 99%
“…One of these antifungal agents is the triazole fluconazole (Flu) (4,10,14,33,34,41). In vivo experimental studies suggested that Flu is active against disseminated candidiasis (8,9,29,31,32,35,37). Recently, the antifungal efficacy of Flu was demonstrated in persistently granulocytopenic rabbits when it was used for prevention or early treatment (39,40).…”
mentioning
confidence: 99%
“…It was reported by Stojanovska et al, that administration of HFD and dexamethasone resulted in higher insulin resistance in rats compared to those treated with dexamethasone alone [22]. This finding could be correlated to the role of HFD in the stimulating of the expression of several proinflammatory cytokines and inflammatory responsive proteins in hypothalamus and this leads to impairment of the insulin-signaling pathway as described by Prada et al, [23].…”
Section: Discussionmentioning
confidence: 64%
“…Metformin (MET) was selected as a reference drug used to treat IR; it was administered orally in a dose of 400mg/kg/day [22]. Doses of fluconazole (20,40mg/kg/day) (FLU 20, 40) were selected and administered orally in accordance with Fisher et al, [23].…”
Section: Rat Aminotransferase (Ast) Colorimetric Kit Was Obtained From Biodiagnostic Comentioning
confidence: 99%
“…Fifteen days after DM induction, rats in groups 3–8 were inoculated intraperitoneally with 0.2 mL of a suspension containing 10 5 colony forming units (CFU)/mL obtained from a clinical C. albicans strain (Fisher et al. 1989 ).…”
Section: Methodsmentioning
confidence: 99%